"El hermano no vota al hermano": la inexistencia del voto confesional y la subrepresentación política de los evangélicos en América Latina = "Brother does not vote for brother" : the non-existence of the confessional vote and the political underrepresentation of the Evangelical in Latin America - Pérez Guadalupe, José Luis (Ciencias sociales y religión, 2020)
The rise of the charismatic and neo-pentecostal movement within American mainline and evangelical churches, and the increasing influence of the new religious right in Latin America, changed the view that evangelicals had about the world and their relationship with it: they went from a clear position of “flight from the world” (the classic fuga mundi) to an unusual position of “conquest of the world” and a militant political participation. In this new context, can we state, as is commonly believed, that “a brother votes for a brother’? Do evangelicals vote for evangelical candidates just because they share the same faith? In this article, we propose that there is no evangelical “confessional vote” in Latin America, not even in Brazil, where we find a “denominational vote” by means of which, at best, “a Pentecostal brother votes for a Pentecostal brother”, “an universalist brother votes for an universalist brother”, “an assembly’s brother votes for an assembly’s brother” and “a baptist brother votes for a baptist brother”. At the same time, we conclude that evangelical political underrepresentation of evangelicals remains. Therefore, there is no direct correlation between the percentage of the evangelical population and the percentage of votes in favor of evangelical candidates in regional electoral processes, and political endorsements are not easy to confirm.